A new species in Aleurodiscus s.l. (Stereaceae, Russulales) from Iran - Ghobad-Nejhad, Masoomeh; Langer, Ewald (Phytotaxa, 2018)
Aleurodiscus persicus sp. nov. is described from Iran, based on phylogenetic analyses of ITS and LSU regions as well as on its morphology. The species is characterized by resupinate, whitish to grayish cream, crustose basidiocarps, a monomitic hyphal system with clamped hyphae, presence of acanthophyses, cylindrical to clavate to submoniliform gloeocystidia, and ellipsoid, amyloid basidiospores measuring ca. 8.3–10 × (4.7–) 5–5.8 µm. The new combination Aleurodiscus graminicola (basionym Gloeomyces graminicola) is proposed.